Citric Juice-mediated Synthesis of Tellurium Nanoparticles with Antimicrobial and Anticancer Properties - Medina Cruz, David; Tien-Street, William; Zhang, Bohan; Huang, Xinjing; Vernet Crua, Ada; Nieto-Argüello, Alfonso; Cholula-Díaz, Jorge L; Martínez, Lidia; Huttel, Yves; Ujué González, María; García-Martín, José Miguel; Webster, Thomas J (Green chemistry : an international journal and green chemistry resource : GC, 2019)
Bacterial infections and cancer are two of the most significant concerns that the current healthcare system should tackle nowadays. Green nanotechnology is presented as a feasible solution that is able to produce materials with significant anticancer and antibacterial activity, while overcoming the main limitations of traditional synthesis. In the present work, orange, lemon and lime extracts were used as both reducing and capping agents for the green synthesis of tellurium nanoparticles (TeNPs) using a microwave-assisted reaction. TeNPs showed a uniform size distribution, and rod- and cubic-shapes, and were extensively characterized in terms of morphology, structure and composition using TEM, SEM, XPS, XRD, FTIR and EDX analysis. TeNPs showed an important antibacterial activity against both Gram-negative and -positive bacteria in a range concentrations from 5 to 50 μg/mL over a 24-hour time period. Besides, nanoparticles showed anticancer effect towards human melanoma cells over 48 hours at concentrations up to 50 μg/mL. Moreover, the Te nanostructures showed no significant cytotoxic effect towards human dermal fibroblast at concentrations up to 50 μg/mL. Therefore, we present an environmentally-friendly and cost-effective synthesis of TeNPs using only fruit juices and showing enhanced and desirable biomedical properties towards both infectious diseases and cancer.